Perilaku Pencarian Informasi Siswa Dalam Memenuhi Kebutuhan Informasi di MAN 2 Deli Serdang - Dewi Maharani; Franindya Purwaningtyas; Miftahul Fikri; Rahmatullaily Sitorus; Muhammad Riski (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine information seeking behavior in meeting information needs at MAN 2 Deli Serdang. This study uses qualitative research methods, using a descriptive analysis approach. The findings of this study, students who meet their information needs prioritize visiting the library rather than going to the internet or other libraries. While the information source that students use the most is the third source of information (tertiary source), namely textbooks (textbooks) compared to the first source of information (primary source) and the second source of information (secondary source). Meanwhile, before conducting an information search, namely by looking at and reviewing the syllabus and preparing some of the notes needed in accordance with the theme of the task (starting). After that they determine the subject and use the core reference to link the search for the desired subject (chaining). Behavior when searching for information, they perform searches on collection shelves, OPAC, and the internet (browsing). The last behavior is that after searching for information, they carry out monitoring, extracting, checking, and ending. The obstacle faced by informants when searching on the internet is the lack of information search strategies applied by them, especially in determining the subject. In addition, the information they get is very much (overloaded). While the obstacles faced in the library are that they often do not get the collections they are looking for because the arrangement and placement on the collection shelves is not appropriate, so they look for other collections. Keywords: Behavior, Search, Information